Economic theory & economic policy in the 20th Century West Indies : 'The Lewis tradition of town and gown' - Best, Lloyd (ECCB BasseterreKN, 1999)
Assesses Sir Arthur Lewis' influence on and contribution to the development of the Caribbean.